Variable sensitivity laser range finder receiver - Saniei, Soodeh Zahab; Mamdoohi, Ghazaleh; Abas, Ahmad Fauzi; Mahdi, Mohd Adzir; Saraf, M. (IEEE (IEEE Xplore), 2011)
A variable sensitivity laser range finder receiver is designed and developed based on variable offset and threshold strategy with noise and dc effect cancellation technique. This receiver operates with 50 ns pulse. The frequency of operation is adjusted to 200 MHz. It means that the time intervals as short as 5 ns can be measured resulting in a distance accuracy of 0.75 m, which is a good accuracy for long distance measurement. FPGA not only converts the time to corresponding distance but also performs high accuracy operation.